DISP-15. TRENDS IN LASER INTERSTITIAL THERMAL THERAPY (LITT): HOW RACE AND SOCIOECONOMIC FACTORS IMPACT ACCESS. (14th November 2022) - Terrell, Danielle; Kandregula, Sandeep; Caskey, Joshua; Newman, Christopher
Abstract: Introduction This study seeks to examine the trends of laser interstitial thermal therapy (LITT) access in the pre-and post-Medicaid expansion time periods; and more specifically, how racial and socioeconomic factors impact access. Methods The National Inpatient Sample (NIS) database was queried for all patients who received LITT from 2010 to 2019 for any indication. Age, gender, race, payer status, and median income by zip code were obtained and compared for the pre-Medicaid expansion (2010-2014), and post-Medicaid expansion (2015-2019) groups. Chi-square analysis was performed for categorical variables, and the student t-test was used to analyze continuous variables. Results The pre-Medicaid expansion (n = 915) and post-Medicaid (n = 3205) time periods were similar in that Whites were the overwhelming majority of LITT recipients (78.7% and 70.8%, p < 0.001). In 2010, all races had low rates of LITT, as would be expected with a new emerging treatment. Although the absolute value of the percentages seems similar, between 2013 and 2014, the proportion of Whites receiving LITT nearly doubled (from 45% to 75%); while all other groups had no significant increase in utilization. Utilization of LITT by Black Americans remained stable, 5.4% and 5.6% in the pre- and post-Medicaid expansion eras, while Hispanics and Others saw slight increases in utilization (8.8% to 10.1% and 7.1% to 13.4% respectively). Although Medicare and Medicaid usage increased over the years, private insurance remained the primary payer for LITT (53.8% and 49.3%, p 0.018). Lastly, patients within the highest income quartiles comprised over half of LITT procedures done in the study period (56.8% and 52.8%, p 0.029). Conclusion Despite nearly a decade and the effects of Medicaid expansion via the Affordable Care Act, LITT is still difficult to access for patients of color, Medicare and Medicaid users, and patients in low-income locales.